REVITALIZING TRADITIONAL METAL CRAFTS: A KNOWLEDGE TRANSFER EMPOWERING SUSTAINABILITY THROUGH BIOMIMICRY DESIGN - Ahmad, Syed Mohd Faisal Syed; Khairi, Hanif; Legino, Rafeah (LOA: Jurnal Ketatabahasaan dan Kesusastraan, 2025)
This paper aims to empower biomimicry design through knowledge transfer for the sustainability of traditional Malay metal crafts, particularly in Malaysia. Recent studies have highlighted a regression in the acceptance and practice of cherished local skills, focusing on the dying art of metalware and jewellery. The primary objective of this project is to ensure the continued practice of metalsmithing by seamlessly integrating traditional craftsmanship with contemporary technological trends by implementing a comprehensive knowledge transfer targeting Malaysia's youth. The concept of "moditional" encapsulates the transition of these traditional practices into modern production methodologies. The core idea behind "moditional" is to expose and educate the local communities in Malaysia on appreciating traditional and modern local craft design. This initiative aligns with the Sustainable Development Goals, explicitly targeting quality education, economic growth, and creating decent work opportunities for all communities. The overarching goal of the knowledge transfer is to facilitate the transfer of skills, experiences, and best practices in computer-aided design (CAD), computer-aided machines (CAM), and craftsmanship. This program encompasses the responsible handling of precious materials, 3D data visualization, prototyping, machining, and hands-on craftsmanship. Through tacit knowledge, it is anticipated that the art of national heritage crafts will thrive and preserve traditional culture in metalware and jewellery. Abstrak Makalah ini bertujuan untuk memberdayakan desain biomimikri melalui transfer pengetahuan untuk keberlanjutan kerajinan logam tradisional Melayu, khususnya di Malaysia. Studi terbaru telah menyoroti kemunduran dalam penerimaan dan praktik keterampilan lokal yang dihargai, dengan fokus pada seni perkakas logam dan perhiasan yang mulai punah. Tujuan utama proyek ini adalah untuk memastikan keberlangsungan praktik pengerjaan logam dengan mengintegrasikan keahlian tradisional dengan tren teknologi kontemporer secara mulus melalui transfer pengetahuan komprehensif yang menyasar generasi muda Malaysia. Konsep "modional" merangkum transisi praktik tradisional ini ke dalam metodologi produksi modern. Inti gagasan di balik "modional" adalah untuk mengekspos dan mengedukasi masyarakat lokal di Malaysia tentang apresiasi desain kerajinan lokal tradisional dan modern. Inisiatif ini sejalan dengan Tujuan Pembangunan Berkelanjutan, yang secara eksplisit menargetkan pendidikan berkualitas, pertumbuhan ekonomi, dan penciptaan lapangan kerja layak bagi seluruh masyarakat. Tujuan utama transfer pengetahuan ini adalah untuk memfasilitasi transfer keterampilan, pengalaman, dan praktik terbaik dalam desain berbantuan komputer (CAD), mesin berbantuan komputer (CAM), dan keterampilan kerajinan. Program ini mencakup penanganan material berharga secara bertanggung jawab, visualisasi data 3D, pembuatan prototipe, pemesinan, dan keterampilan kerajinan tangan. Melalui pengetahuan tacit, diharapkan seni kerajinan warisan nasional akan berkembang dan melestarikan budaya tradisional dalam bidang logam dan perhiasan. Kata-kata Kunci: Biomimikri; Kerajinan Tradisional Melayu; Kerajinan Logam; Teknologi; Transfer Pengetahuan